Immune checkpoint pathways in glioblastoma: a diverse and evolving landscape - Inocencio, Julio F.; Mitrasinovic, Stefan; Asad, Mohammad; Parney, Ian F.; Zang, Xingxing; Himes, Benjamin T. (Frontiers in Immunology, 2024)
Immune checkpoint (IC) inhibition in glioblastoma (GBM) has not shown promising results in the last decade compared to other solid tumors. Several factors contributing to the lack of immunotherapy response include the profound immunosuppressive nature of GBM, highly redundant signaling pathways underlying immune checkpoints, and the negative immunogenic impact of current standard of care on the tumor microenvironment. In this review, we will discuss various ICs in the context of GBM, their interplay with the tumor immune microenvironment, relevant preclinical and clinical studies, and the impact of current treatment modalities on GBM IC blockade therapy. Understanding the molecular mechanisms that drive ICs, and how they contribute to an immunosuppressive tumor microenvironment is critical in advancing IC inhibition therapy in GBM.Furthermore, revisiting current treatment modalities and their impact on the immune landscape is instrumental in designing future combinatorial therapies that may overcome treatment resistance.